2022
DOI: 10.48550/arxiv.2203.12992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LS Algebras, Valuations and Schubert Varieties

Abstract: In this paper, we propose an algebraic approach via Lakshmibai-Seshadri (LS) algebras to establish a link between standard monomial theories, Newton-Okounkov bodies and valuations. This is applied to Schubert varieties, where this approach is compatible with the one using Seshadri stratifications in [4], showing that LS paths encode vanishing multiplicities with respect to the web of Schubert varieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…LS-algebras and valuations. The second step of our project (see [10]) showed that an LS-algebra may be defined in terms of valuations and a quasi-valuation as well. Also in this case one recovers the generators of the algebra via valuations having at most one-dimensional leaves, the quasi-valuation is additive on standard monomials and the straightening relations have a clear interpretation in terms of the quasi-valuation.…”
Section: Standard Monomial Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…LS-algebras and valuations. The second step of our project (see [10]) showed that an LS-algebra may be defined in terms of valuations and a quasi-valuation as well. Also in this case one recovers the generators of the algebra via valuations having at most one-dimensional leaves, the quasi-valuation is additive on standard monomials and the straightening relations have a clear interpretation in terms of the quasi-valuation.…”
Section: Standard Monomial Theorymentioning
confidence: 99%
“…See also Conclusion 5.5 for connections with the present formulation. For the details with respect to the following formulation see [4], [6] and [10].…”
mentioning
confidence: 99%